Enhancing the Performance and Competitiveness of Women in MSMES Through Marketing, Capital, and Digital Literacy - Priambodo, Aji; Sulaeman, Maman; Permana, Indra; Sugiarto, Irwan (Universitas Bina Sarana Informatika, 2024)
The main objective of this study is to investigate the factors that influence the performance and competitiveness of women entrepreneurs in the Tuka Tuku Purbalingga programme. Tuka-Tuku in Purbalingga serves as support for the development of start-ups in the field of local culinary specialties or other local products. Tuka-Tuku facilitates the expansion of local start-ups, preserves the authenticity of regional products, and promotes the cultural heritage of diverse culinary traditions. The current study employed a quantitative research design utilizing a survey method to gather data. The survey instrument comprised a 5-point Likert scale and was administered to female entrepreneurs participating in the program. To test ten research hypotheses pertaining to the relationships between marketing, capital, digital literacy, performance, and competitiveness, Structural Equation Modeling was applied. The findings of this research have revealed that marketing, financing, and digital literacy play a significant and positive role in enhancing the performance and competitiveness of women entrepreneurs participating in the Tuka Tuku Purbalingga program. Additionally, this study confirms that performance is a crucial determinant of female entrepreneurs' competitiveness in the program. These findings suggest that women entrepreneurs with strong marketing, financing, and digital literacy skills are more likely to achieve better performance and be more competitive in the market. Given these results, it is recommended that policymakers and stakeholders direct their efforts towards enhancing the marketing, capital, and digital literacy skills of female entrepreneurs in the Tuka Tuku Purbalingga program to improve their overall performance and competitiveness.